Enhancement of β-Glucosidase Activity in Penicillium sp. by Random Mutation with Ultraviolet and Ethyl Methyl Sulfonate - Syafriana, Vilya; Nuswantara, Sukma; Mangunwardoyo, Wibowo; Lisdiyanti, Puspita (BRIN, 2014)
The genus Penicillium has a potential ability to produce β-glucosidase. The aim of the study was to improve the β-glucosidase activity of Penicillium sp. ID10-T065 with physical (Ultraviolet = UV), chemical (Ethyl Methyl Sulfonate = EMS), and combined mutation (UV-EMS). The spores of Penicillium sp. ID10-T065 were exposed into UV irradiation for 3 minutes with dose of 0.1 J/cm2 and 13 cm of distances. Chemical mutation was done by treated spores into 3% of EMS solution for an hour. Combined mutation of UV and EMS were also performed by UV for 3 minutes (0.1 J/cm2, 15 cm) and continued with soaking into 2-3% of EMS solution. The developed mutants were screened, selected and assayed. Comparison of enzyme activities with the wild- type (1.78 U/ml), mutant UV13 (5.53 U/ml) showed a 3.1 fold increase; mutant EM31 (4.26 U/ml) showed a 2.4 fold increase. Meanwhile, mutant UM23 obtained from the multiple exposures showed a decreased activity (1.75 U/ml). Mutant UV13 showed the best enzyme activity to be considered as a potential strain for β-glucosidase producer. This result needs to be further elaborated especially on its genetic stability studies in order for the ascertained as a stable mutant.